2022
DOI: 10.1021/acs.jced.2c00263
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Density and Viscosity of Diisopropyl Ether and 1-Alkanol Mixtures at Various Temperatures

Abstract: The current study was aimed to investigate intermolecular forces in six binary associating systems containing diisopropyl ether (DIPE) and normal alcohols (1-pentanol to 1-decanol) at 293.15–323.15 K. The density and viscosity of binary fluids were measured, and excess functions and partial volumes were calculated. Excess volumes and deviation in the viscosity are negative for all the above solutions. Intermolecular forces in mixtures are adjusted by molecular packing, dispersion forces, and hydrogen bonding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The pure parameters for the PC-SAFT model are typically determined from experimental data. In this study, data for alcohols and 1,3-dioxolane were obtained from previous research , as they are indicated in Table . To improve the precision of the forecasts for the binary mixtures, the interaction parameter k ij was determined by the implementation of the subsequent equation. ε i j = ε i ε j ( 1 k i j ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pure parameters for the PC-SAFT model are typically determined from experimental data. In this study, data for alcohols and 1,3-dioxolane were obtained from previous research , as they are indicated in Table . To improve the precision of the forecasts for the binary mixtures, the interaction parameter k ij was determined by the implementation of the subsequent equation. ε i j = ε i ε j ( 1 k i j ) …”
Section: Resultsmentioning
confidence: 99%
“…Both 1,3-dioxolane and the alcohols had a mass fraction purity of greater than 99.5%, as shown in Table . Experimental measurements of density and viscosity for pure 1,3-dioxolane were performed in this study, while data for the 1-alkanol were obtained from our previous work. A comparison of the density and viscosity values for 1,3-dioxolane obtained in this study with those reported in the scientific literature is given in Table .…”
Section: Experimental Sectionmentioning
confidence: 97%
See 1 more Smart Citation